The Effect Of SMART (Self Monitoring Approach To Reading And Thinking) And Self-Efficacy Toward The Reading Skill On Narrative Texts On First Grade Students Of SMAN 10 Pekanbaru - Agustiani, Aulia (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2021)
In teaching reading, teaching strategy and students’ self-efficacy influence students’ reading comprehension. The research was conducted to find out the effect of SMART (Self Monitoring Approach to Reading and Thinking) and students’ self efficacy on students’ reading comprehension of narrative texts. The design of this research was quasi experimental with 2x2 factorial design. The population of this research was the first grade students of SMAN 10 Pekanbaru, 2015/2016 academic year. Reading comprehension test and self-efficacy questionnaire were used as research instruments. Then, the data were analyzed using t-test formula and two ways Anova. The result of this research shows that (1) students who were taught by using SMART (Self Monitoring Approach to Reading and Thinking) had better reading comprehension of narrative texts than those who were taught by using Small Group Discussion. It was proven by result of t-test which showed that tobserved (2.23) was bigger than ttable (1.989), (2) students who had high reading self-efficacy taught by using SMART (Self Monitoring Approach to Reading and Thinking) had better reading comprehension of narrative texts than those who were taught by Small Group Discussion, (3) students who had low reading self-efficacy taught by using SMART (Self Monitoring Approach to Reading and Thinking) had better reading comprehension of narrative texts than those who were taught by Small Group Discussion, and (4) there was no interaction between both strategies and students’ self efficacy toward students’ reading comprehension, where Fobserved (0.69) was less than Ftable (3.23). As conclusion, SMART (Self Monitoring Approach to Reading and Thinking) had a significant result on students’ reading comprehension than Small Group Discussion and there was no interaction between teaching strategies and reading self-efficacy on students’ reading comprehension.